The Effect of Cafe Atmosphere on Purchase Decisions Through Purchase Intention as an Intervening Variable at The Café Kopi Kenangan Merak in Samarinda - Amelya, Yunita; Istimaroh, (Research in Management of Technology and Business, 2024)
This study found that with increasing competition in the coffee outlet industry, Cafe Kopi Kenangan needs to maintain its marketing strategy by improving the quality of the atmosphere in its outlets. This study aims to determine the effect of Café Atmosphere on Purchase Decisions through Purchase Intention as an intervening variable at Café Kopi Kenangan Merak in Samarinda. The population in this study are consumers who have purchased products at Café Kopi Kenangan and have bought at Café Kopi Kenangan. This research uses descriptive quantitative type. The sample used in this study was 213 respondents who were taken by probability sampling method using simple random sampling. The data collection technique was carried out using a questionnaire in the form of a Google Form link. The data processing method of this research is using SmartPLS 4.0.2 software. The results in this study indicate that café atmosphere has a positive and significant effect on purchase decision, café atmosphere has a positive and significant effect on purchase intention, purchase intention has a positive and significant effect on purchase decision, café atmosphere has a positive and significant effect on purchase decision through purchase intention as an intervening variable.